Return on Investment in Education. Case Study on Education in Romania - Pribac, Loredana Ioana; Anghelina, Andrei; Blaga, Radu Lucian (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2016)
The aim of this study is to develop, test and validate based on a conceptual research model, the influence of education on the GDP/ capita, starting from relevant theories and empirical models from literature or implementing additional impact models and variables. Building on the model developed by Mincer (1995) on the yield rates of investment in education, we applied econometric models for Romania, for the period 1960-2010. The results led to a main conclusion, namely, the importance of investment in education is undeniable, it has positive effect on the economic growth of Romania.